Prevalence of CagA-positive Helicobacter pylori strain and H. pylori-associated gastritis activity in Tuva schoolchildren of different age groups - Tamara V. Polivanova; Vitaly A. Vshivkov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To study the prevalence of CagApositive Helicobacter pylori (H. pylori) strain and to estimate activity of gastritis associated to this infection in schoolchildren presenting their dyspeptic complains in indigenous and extraterrestrial populations of Tuva republic. Material and methods. In 218 randomly selected schoolchildren (106 of them were extraterrestrial, 112 - native born) of overall 1064 children living in two settlements of the Tuva republic prevalence of CagA-positive H. pylori strain was studied. Inflammatory activity of the stomach body and antrum mucosa was studied in 59 Tuvinians and 72 Caucasians included in the study, according to predefined age groups (7-11 and 12-17 years). Results. Increase in the rate of CagA-seropositive children in local population was found to a large extent due to expense of junior children. Age-related increase in CagA-positive H pylori infection in specific ethnic group was insignificant. Antrum mucosa information in CagAseropositive children of extraterrestrial population was characterized by higher activity irrespective to age. That is not found in indigenous population. At CagAseropositive schoolchildren in both ethnic populations activity of corpus gastritis increased along with age. Conclusion. The received results demonstrate that development, course and progression of CagA-positive H. pylori associated gastritis is affected by genetic (ethnic) features of the host.